Predicting Category Purchase Behaviour: An Analysis of Image-Enhancing Products and Customer Personality Traits - Zlatic, Karly (2018)
Every day people look in the mirror to adjust his or her appearance. Some people glance every chance they get. Appearance is often modified through use of products: face cosmetics, tanning oils, or even diet pills. In some cases, though, purchasing can be extreme in order to cover up perceived “flaws” due to disordered thinking, such as in the incidence of those with body dysmorphic disorder. Research has shown that people with differing dispositions spend money in order to fit their own needs and desires. Drawing on these concepts, this study extends the research by arguing that individual differences in personality impact consumer spend on appearance modifying products. Through analysis using more than 2,500 loyalty accounts from a leading health and beauty retail corporation, this study shows that some personality traits are correlated with and can be used to predict image-modifying product purchases. Specifically, results show that the effect of age plays a particularly influential role in face cosmetics purchases. In summary, customer traits relate to trends of customers’ image-based product purchases, but personality does not define and perfectly predict these patterns.